2011
DOI: 10.1007/s00424-011-0936-3
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic effect of linoleic acid on connexin 46 hemichannels

Abstract: Connexins form hemichannels at undocked plasma membranes and gap-junction channels (GJCs) at intercellular contacting zones. Under physiological conditions, hemichannels have low open probabilities, but their activation under pathological conditions, such as ischemia, induces and/or accelerates cell death. Connexin 46 (Cx46) is a major connexin of the lens, and mutations of this connexin induce cataracts. Here, we report the effects of linoleic acid (LA) on the electrical properties of Cx46 GJCs and hemichanne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 55 publications
0
34
0
Order By: Relevance
“…This dual mechanism was also observed in the muscle rNa(V)1.4 channel isoform, which appears to depend on the depolarizing potential: AA, but not its metabolites, increased the channel current evoked by a −30 or −40 mV depolarization of the membrane potential, but significantly decreased it by a depolarization over −10 mV (Gu et al, 2009). It was also reported that cis -unsaturated FFA with a double bond at position 9 have a biphasic effect on connexin 46 hemichannels: current activation at low FFA concentration and current inhibition at higher concentrations, the effect being directly proportional to the number of double bonds (Retamar et al, 2011). The authors ruled out the possibility that the biphasic effect was mediated by changes in the biophysical properties of the plasma membrane.…”
Section: Ffa Effects On Voltage-gated Ion Channelsmentioning
confidence: 98%
See 1 more Smart Citation
“…This dual mechanism was also observed in the muscle rNa(V)1.4 channel isoform, which appears to depend on the depolarizing potential: AA, but not its metabolites, increased the channel current evoked by a −30 or −40 mV depolarization of the membrane potential, but significantly decreased it by a depolarization over −10 mV (Gu et al, 2009). It was also reported that cis -unsaturated FFA with a double bond at position 9 have a biphasic effect on connexin 46 hemichannels: current activation at low FFA concentration and current inhibition at higher concentrations, the effect being directly proportional to the number of double bonds (Retamar et al, 2011). The authors ruled out the possibility that the biphasic effect was mediated by changes in the biophysical properties of the plasma membrane.…”
Section: Ffa Effects On Voltage-gated Ion Channelsmentioning
confidence: 98%
“…The authors ruled out the possibility that the biphasic effect was mediated by changes in the biophysical properties of the plasma membrane. They concluded that activation and inhibition current mechanisms involve different sites of action (Retamar et al, 2011). …”
Section: Ffa Effects On Voltage-gated Ion Channelsmentioning
confidence: 99%
“…However, the activation or opening of these channels is involved in autocrine/paracrine signaling, which provides a pathway for release of ATP (Cotrina et al, 1998), glutamate (Ye et al, 2003), NAD + (Bruzzone et al, 2001) and prostaglandins (Cherian et al, 2005), and mediate various aspects of cell signaling and function. Hemichannel activity is regulated by posttranslational modifications of connexin subunits, e.g., S-nitrosylation, phosphorylation and dephosphorylation (Contreras et al, 2003; Retamal et al, 2006), membrane physiochemical conditions, e.g., membrane voltage, pH, mechanical stimulation and concentrations of monovalent and divalent cations (Burra et al, 2010; Schalper et al, 2010; Siller-Jackson et al, 2008) and by extracellular signaling molecules, e.g., ATP, FGF1/2 and lipophilic molecules (Garre et al, 2010; Kar et al, 2012; Retamal et al, 2011; Schalper et al, 2012). In addition to connexin hemichannels, pannexins also form channels with similar molecular stoichiometry and permeability properties as connexin hemichannels.…”
Section: Connexin Hemichannelsmentioning
confidence: 99%
“…However, knowledge about the regulation of HCs (or GJCs) by FFAs in the epithelium of the gastrointestinal tract is very limited and is incompletely understood in other cell types [21-24]. …”
Section: Introductionmentioning
confidence: 99%
“…Linoleic acid (LA) has been shown to modulate the functional state of Cx46 HCs [21]. Moreover, in HeLa cells transfected with different Cxs, our group reported that LA increases Cx26, Cx43 and Cx45 HC activity, and this effect is associated with elevated intracellular free Ca 2+ concentration and activation of the PI3K/Akt-dependent pathway [24].…”
Section: Introductionmentioning
confidence: 99%